Prevalence and Risk Factors Associated with Suicide Ideation and Attempts in Korean College Students - Lee, Hong-Seok (Korean Neuropsychiatric Association, 2008)
OBJECTIVE: Suicide is a leading cause of death in college age students. Identification of the associated risk factors has important implications for how to prevent and respond to this population; however, few studies have been performed on this topic in this age group. The purpose of this study was to evaluate the prevalence and risk factors associated with suicide ideation and attempts in college students. METHODS: Three hundred sixty-eight college students participated in this cross-sectional observational study. The recent (over two weeks) suicide ideation and lifetime suicide attempts were defined according to Moscicki's suicide behavior index. Sociodemographic variables were assessed and psychopathology measured using the Beck Depression Inventory, the Bipolar Spectrum Diagnostic Scale and the Alcohol Use Disorders Identification Test. A hierarchical multiple logistic regression analysis was used to identify the significant risk factors related to suicide ideation and attempts. RESULTS: The two-week prevalence of suicidal ideation was 9.8%, and the lifetime prevalence of suicide attempts was 3.3%. The univariate analysis showed that students who had more severe depression (p<0.001), a higher probability for bipolar disorder (p<0.001) and decrement of academic achievement (p<0.005) were more likely to have suicide ideation. Those with factors such as severe depression (p<0.05), a higher probability of bipolar disorder (p<0.001), a low socioeconomic status (p<0.001), who lived alone (p<0.01), and were female (p<0.05) had a higher risk for suicide attempts. The most important predictors of suicide ideation, by the logistic regression analysis, were depression, probability for bipolar disorder and academic achievement, and the risks identified for suicide attempts were socioeconomic status and probability of bipolar disorder. CONCLUSION: Suicide ideation and attempts were common in college students. The results of this study suggest that early identification and management of mood disorders and other sociodemographic risk factors may have implications for intervention and prevention.